Biodistribuição do pertecnetato de sódio após cirurgia do Switch Duodenal - Araújo Filho, Irami (2007)
The biliopancretic diversion with duodenal switch is one of the mixing techniques used in the treatment of morbid obesity. The duodenal switch reduces the stomach capacity and leaves only 50-100 cm of small intestine for nutrition and absorption. The surgery produces hormonal, structural and biochemical changes, which can influence on the result of scintigraphic examinations in operated patients. With the objective of evaluate the postoperative biodistribution of sodium pertechnetate (Na99mTcO4) in brain, thyroid, heart, lung, liver, spleen, kidney, stomach, duodenum, pancreas, small intestine, bladder, muscle and bone of Wistar rats. The rats were randomly allocated into 3 groups of 7 rats each: the duodenal switch group (DS), the control group (C) and the sham group (S). They were operated under anesthesia and aseptic technique. In the tenth postoperative day, 0.1mL of sodium pertechnetate was injected via orbital plexus. After 30 min the animals were killed with overdose of anesthetic and samples of liver, spleen, pancreas, stomach, duodenum, small intestine, thyroid, lung, heart, kidney, bladder, muscle, bone and brain were harvested, washed with saline and weighed. The detention of radioactivity was made using the automatic Gamma Counter Wizard, PerkinElmer and the percentage of activity per gram of tissue (%ATI/g) was calculated. There was no early or late mortality in either rats groups. The values of percent radioactivity per gram of tissue (%ATI/g), showed no significant difference in liver, stomach, small bowel, duodenum, kidney, heart, bladder, bone and brain, when compared the DS rats with sham and controls rats. A postoperative significant increase in mean %ATI/g levels was observed in spleen, pancreas and muscle in group DS rats, as compared to group S and C rats (p<0.05). In the lung there was an increase and in thyroid a decrease in mean %ATI/g of DS rats, when compared to sham rats (p>0.05). In conclusion, the biliopancreatic diversion with duodenal switch in rats modified the biodistribution of sodium pertechnetate in thyroid, lung, pancreas, spleen and muscle. The study had the participation of the departments and laboratories researches, as Nucleus of Experimental Surgery, Department of Surgery, Laboratory of Radiobiology, Department of Pathology and Service of Nuclear Medicine, certifying the character of a multidisciplinary research